The body and its parts. The legal allocation of human biological materials - Tallacchini, Mariachiara (Medicina e Morale, 1998)
Recent developments in biotechnology have threatened the traditional legal view of the human body and its elements, and raise questions that have not been previously answered. The human body seems to be a new, strange legal object, because it oscillates between different conditions. Indeed, from a legal point of view, it is at the center of several dilemmas: the human body can be perceived as a legal subject and/or a legal object; body parts can be considered equal or different between them; the creation of human bioproducts poses the problem of the artificialization and patenting of the human body. The legal status of discarded parts of the body is discussed here, in order to build a consistent scheme regarding them. The consideration of human tissues within the concept of property rights raises many problems and harms the idea of human dignity. The only feature that body parts seem to share is their common nature of res extra commercium, but the exclusion of the economic mode of valuation is not enough to draw a sound regulation for the donation or for medical and research uses of human biological materials. We need a more comprehensive and coherent legal scheme, which values the human body both as a symbol of community and in terms of sharing, while respecting the freedom and dignity of donors.